Myśl społeczna Kardynała Augusta Hlonda. Wybrane zagadnienia - Skorowski, ks. Henryk (Annales. Etyka w Życiu Gospodarczym, 2010)
The present article undertakes the theme of social thought of Cardinal Hlond. It presents the questions of social engagement of Catholics, the problems of the family, the theory of the nation as well as the concept of the state.The problem of the Catholic engagement is the important element of Cardinal Hlond’s social teaching. It appears in the multidimensional perspective. One can find here the political, the socio-economic dimensions as well as the cultural one. The culture is understood here in a very wide sense. All the activities leading to the person’s spiritual, intellectual and moral development belong to it.The second important topic of Cardinal Hlond’s social teaching are family issues. The family is understood as the environment of moral and religious development of every person. It transforms, builds and improves family life as well as every human being’s dignity.Another important subject is the concept of nation. For Hlond nation is the natural environment of the individual’s development. Two fundamental elements describe the notion of nation: community and culture. They are carriers the moral, religious, intellectual and spiritual values.The final important point of Cardinal Hlond’s social teaching is the concept of state. For the Cardinal the state should be always at the service in the relations to citizens. The role of the state appears in three dimensions. First, to create living conditions for every citizen; second, to guarantee the fundamental and natural law of freedom; third, to create the „space” of self-realization, which manifests itself in public life activity.